2014
DOI: 10.1130/g34802.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental generation of volcanic lightning

Abstract: Explosive volcanic eruptions are commonly associated with intense electrical activity and lightning. Direct measurement of the electric potential at the vent, where the electric activity in the volcanic plume is fi rst observed, is severely impeded, limiting progress in its investigation. We have achieved volcanic lightning in the laboratory during rapid decompression experiments of gas-particle mixtures under controlled conditions, and recorded it using a high-speed camera and two antennas. We fi nd that ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
95
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 26 publications
13
95
0
Order By: Relevance
“…Laboratory studies of electrical charging of volcanic ash systems confirm that the particle size distribution plays an important role in the electrical charging of terrestrial volcanic plumes (Houghton et al 2013;Cimarelli et al 2014) and indicate that the composition of the particulate matter making up the plume also affects electrical charging. The factors that affect triboelectric charging in terrestrial volcanic plumes, namely the particle size distribution, particle composition and relative humidity, are expected to have similar effects in the aeolian Martian environment.…”
Section: Charging and Radioactivity In Volcanic Plumesmentioning
confidence: 98%
“…Laboratory studies of electrical charging of volcanic ash systems confirm that the particle size distribution plays an important role in the electrical charging of terrestrial volcanic plumes (Houghton et al 2013;Cimarelli et al 2014) and indicate that the composition of the particulate matter making up the plume also affects electrical charging. The factors that affect triboelectric charging in terrestrial volcanic plumes, namely the particle size distribution, particle composition and relative humidity, are expected to have similar effects in the aeolian Martian environment.…”
Section: Charging and Radioactivity In Volcanic Plumesmentioning
confidence: 98%
“…The electric field of dust devils, for example, is known to point upward, consistent with smaller, negatively charged grains being lifted higher into the air [3]. A similar mechanism is suspected to be responsible for the large electric fields and consequent lightning generated in volcanic ash clouds [4][5][6][7][8]. Zhao et al showed that the charge-to-mass ratio for a variety of powder samples crossed from negative to positive as the particle diameter increased, indicating a similar trend [9].…”
mentioning
confidence: 95%
“…More importantly, if traps did exist in this range, they would be susceptible to un- loading via visible light (∼ 1.8−3.1 eV). This discrepancy is especially relevant to granular systems continually exposed to visible light from the sun, such as wind-blown dust or volcanic ash, which exhibit strong, same-material tribocharging behavior [3][4][5][6][7][8][31][32][33][34]. We also considered the implications of possible size-dependent electric discharging, which might occur when the electric field at the surface of a particle exceeds the dielectric strength of the surrounding gas.…”
mentioning
confidence: 99%
“…Thus, volcanic lightning may provide a valuable monitoring tool for active volcanoes, allowing detection of ash emissions from safe distance and in inclement weather conditions [Behnke and McNutt, 2014]. However, the use of volcanic lightning to probe the properties of volcanic plumes (ash concentration, mass eruption rate, turbulence, etc) has been hampered so far largely by (i) the lack of systematic instrumental observation of electric activity in volcanic plumes and (ii) the limited number of experimental investigations on the electrification processes of volcanic materials [James et al, 2000;Houghton et al, 2013;Méndez-Harper et al, 2015] and the mechanism of plume electrification [Cimarelli et al, 2014].…”
Section: Introductionmentioning
confidence: 99%